Comorbid Mental Disorders in Fetal Alcohol Spectrum Disorders: A Systematic Review. Issue 4 (May 2017) - Weyrauch, Deland; Schwartz, Megan; Hart, Brandon; Klug, Marilyn G.; Burd, Larry
ABSTRACT: Objective: A systematic review of published literature to estimate prevalence of comorbid mental disorders in fetal alcohol spectrum disorders (FASDs) and compare with general population prevalence estimates. Methods: A PubMed search was used to locate articles reporting on FASD and mental disorders published through June 2015. Next, lists of published studies from all issues of the National Organisation for Foetal Alcohol Syndrome—UK publication Fetal Alcohol Forum—were searched. Weighted average prevalence was estimated for the comorbid mental disorders with sufficient data for analysis. We then compared prevalence of mental disorders in the FASD population with rates in the mental health literature. Results: We identified 26 articles reporting 5984 cases of FASD. Of the 15 comorbid mental disorders, 11 had sufficient data for inclusion in the analysis. Attention-deficit/hyperactivity disorder occurred in 50% of persons with FASD (10 times the expected rate). Intellectual disability occurred at 23 times the expected rate. In 5 of the 12 disorders, rates in the FASD population significantly exceeded expected rates by 10% to 45%. Conclusion: Increased rates of mental disorders in people with FASD are commonly reported. Mental health providers should routinely consider FASD in the diagnosis and management of mental illness and developmental disorders. The quality of the research and precision of comorbidity estimates would be improved by additional studies including people with FASD and non-FASD comparison subjects. Until these studies are available, this review provides the best available estimates of comorbid mental disorders in people with FASD.